ZCMGenerator: Generation of ZCM Models from ZC2M Metamodel Based on MDA and ADM Approaches - Mamouni, Abdelaziz; Marzak, Abdelaziz; Belangour, Abdessamad; Azouazi, Mohamed; Youness, Raki; Al haddad, Zayed (Transactions on Engineering and Computing Sciences, 2017)
Zakat Calculation Models (ZCM) consist of sequences of specific concepts of the Zakat domain such as category, sub-category, wealth and rate. The content of a ZCM model depends on the school of jurisprudence and the type of Zakatable wealth. Correspondingly, creating a ZCM model involves four steps (analyzing, modelling, developing and generating), the last step consists of generating ZCM model in a structured XML format in accordance with our ZC2M (Zakat Calculation Meta-Model) metamodel which we have already proposed in our previous work. This paper proposes ZCMGenerator, a metamodel-based framework for modelling and generating of the ZCM models adaptable to the new technologies and specific to each school of jurisprudence. These models are extensible, reusable, portable, and can be communicated to any platform without taking into account technical specifications. This paper also presents some cases study scenarios emphasizing the benefits enabled by the proposed framework and a detailed comparison between ZCMGenerator and some existing ZCP (Zakat Calculation Platforms) platforms. Experimental results show that, compared with traditional ZCP platforms, ZCMGenerator is more scalable and high-performance.